Factors influencing smallholder participation in commercial tree growing outgrower schemes: The case of Namwasa outgrower scheme in Uganda - Sherry Kyamagero; Kendisha Soekardjo Hintz; Nelson Turyahabwe; Gerald Kapp (Trees, Forests and People)
Over the past 30 years, outgrower/contract farming has been promoted as an institutional innovation to boost agricultural and farm forestry in less developed countries. Understanding factors that make outgrower arrangements beneficial is crucial to realizing their full potential. This study examines a commercial tree-growing outgrower scheme in Uganda, assessing socioeconomic factors influencing farmers' participation and their motivations. Data collection utilized a mixed-method approach, including semi-structured interviews (n = 80), focus group discussions, and key informant interviews. Findings revealed that participation was significantly associated with the purpose for the trees (χ2 = 19.7875, p = 0.00005), membership in farmer-based organizations (χ2 = 76.05, p = 2.77E-18), and household size (χ2 = 14.12667, p = 0.000856). Key motivations were access to quality seedlings, rated very important by 95 % of respondents, and farm credits, rated very important and important by 43.8 % and 36.3 % of farmers, respectively. Additionally, 96.3 % and 95 % considered training in agrochemical application and in planting, maintenance, and harvesting techniques, respectively, as very important. Most farmers (93 %) preferred on-spot cash payment over payment in kind. 55 % of farmers preferred donation with charge while 45 % preferred purchasing inputs at a subsidized price. Most farmers (65 %) favored a cost-sharing arrangement for harvesting costs, and 98 % wanted the company to cover post-harvest expenses. This study highlights the need of considering farmers' socioeconomic characteristics and preferences for contractual arrangements when designing outgrower schemes, as well providing seedlings, financial support, and training to enhance participation.